Colonization with multidrug‐resistant organisms is associated with impaired survival of patients with surgically resected cholangiocarcinoma. (7th December 2022) - Kinzler, Maximilian N.; Stehle, Angelika; Schulze, Falko; Hogardt, Michael; Wichelhaus, Thomas A.; Kempf, Volkhard A. J.; Finkelmeier, Fabian; Trojan, Jörg; Zeuzem, Stefan; Schnitzbauer, Andreas A.; Bechstein, Wolf O.; Wild, Peter J.; et al.
Abstract: Background & Aims: Colonization with multidrug‐resistant organisms (MDRO) has been shown to impair survival in patients with various malignancies. Despite the increasing spread of MDRO, its impact on patients with cholangiocarcinoma (CCA) is unclear. Aim of this study was to analyse the impact of MDRO‐colonization on overall prognosis in CCA patients. Methods: All patients with surgically resected CCA diagnosed between August 2005 and November 2021 at the University Hospital Frankfurt were screened for MDRO. CCA patients with a positive MDRO screening before or within the first 90 days after diagnosis of CCA were defined as colonized. Patients with a negative MDRO screening were defined as non‐colonized. Results: Hundred and sixty nine patients were included. 32% ( n = 54) were screened MDRO positive, while 68% (115) were non‐colonized. Median overall survival (OS) for colonized patients was 17.1 months (95% CI = 9–25.2 months) compared to 50 months (95% CI = 37.1–62.8) for MDRO‐negative patients ( p ≤ .001). Non‐cancer‐related mortality ( p ≤ .001) and infectious‐related death ( p ≤ .001) was significantly higher in the MDRO‐colonized group. In multivariate analysis, MDRO colonization (HR = 2.1, 95% CI = 1.4–3.3, p = .001), ECOG 1 (HR = 2.5, 95% CI = 1.6–4, p ≤ .001) and N1 status (HR = 1.7, 95% CI = 1.1–2.6, p = .017) were independent risk factors for OS. Conclusion: MDRO‐colonization contributes to poor survival in patients with surgically resected CCA. MDRO surveillance is necessary to optimize clinical management of infections and to potentially reduce mortality in this critical population.